NLRP3 inflammasome activation by Foot-and-mouth disease virus infection mainly induced by viral RNA and non-structural protein 2B. Issue 3 (3rd March 2020) - Zhi, Xiaoying; Zhang, Yun; Sun, Shiqi; Zhang, Zhihui; Dong, Hu; Luo, Xin; Wei, Yanquan; Lu, Zengjun; Dou, Yongxi; Wu, Run; Jiang, Zhengfan; Weng, Changjiang; et al.
ABSTRACT: Foot-and-mouth disease virus (FMDV) is a positive-strand RNA virus of the family Picornaviridae . Early studies show that some viruses of Picornaviridae, such as EMCV and EV71, induce NLRP3 inflammasome activation. Our current study demonstrates that FMDV induces the secretion of caspase-1 and interleukin 1 beta (IL-1β), as well as activates the NLRP3 inflammasome in a dose- and time-dependent manner. Meanwhile, NLRP3 inflammasome can suppress FMDV replication during virus infection. Both FMDV RNA and viroporin 2B stimulate NLRP3 inflammasome activation. FMDV RNA triggers NLRP3 inflammasome through p-NF-κB/p65 pathway not dependent on RIG-I inflammasome. FMDV 2B activates NLRP3 inflammasome through elevation of intracellular ion, but not dependent on mitochondrial reactive oxygen species (ROS) and lysosomal cathepsin B. It further demonstrates that 2B viroporin activates NLRP3 inflammasome and induces IL-1β in mice, which enhances the specific immune response against FMDV as an ideal self-adjuvant for FMD VLPs vaccine in guinea pigs. The results reveal a series of regulations between NLRP3 inflammasome complex and FMDV. Amino acids 140–145 of 2B is essential for forming an ion channel. By mutating the amino acid and changing the hydrophobic properties, the helical transmembrane region of the viroporin 2B is altered, so that the 2B is insufficient to trigger the activation of NLRP3 inflammasome. This study demonstrates the functions of FMDV RNA and 2B viroporin activate NLRP3 inflammasome and provides some useful information for the development of FMD vaccine self-adjuvant, which is also helpful for the establishment of effective prevention strategies by targeting NLRP3 inflammasome.